Pengelolaan Tata Ruang Kantor pada Dinas Pemuda dan Olahraga Kota Bogor - Dewi Nur Anggraeni; Christian Wirdendi Wolor; Adnan Kasofi (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research is located at the Youth and Sports Office of Bogor City and is focused on knowing how the process of managing office space, identifying the obstacles faced, and exploring the solutions applied in the management. The method used in this research is descriptive qualitative with a case study approach to obtain a comprehensive picture of the condition of office layout. The subjects in this study were general employees who had direct involvement in the management and utilization of work space. Data collection techniques were conducted through observation, interviews, and documentation. The findings of this study indicate that spatial management has not been running optimally, as seen from the inefficient spatial arrangement, limited workspace capacity, and not maximizing the utilization of comfort support elements such as lighting, air ventilation, and aesthetic aspects of the room. The main obstacle found is the physical condition of the building which is an old building and is not fully in accordance with the current office spatial needs. Efforts made by the agency include a needs assessment in the budgeting process based on applicable public service needs standards, as well as maximizing the use of available space to support service efficiency and effectiveness. Therefore, the results of this study are expected to be a reference and consideration for agencies in developing their office space.